When and why narcissists exhibit greater hindsight bias and less perceived learning - HOWES, Satoris S. (Institutional Knowledge at Singapore Management University, 2020)
The present research sought to examine the impact of narcissism, prediction accuracy, and should counterfactual thinking—which includes thoughts such as “I should have done something different”—on hindsight bias (the tendency to exaggerate in hindsight what one knew in foresight) and perceived learning. To test these effects, we conducted four studies (total n = 727). First, in Study 1 we examined a moderated mediation model, in which should counterfactual thinking mediates the relation between narcissism and hindsight bias, and this mediation is moderated by prediction accuracy such that the relationship is negative when predictions are accurate and positive when predictions are inaccurate after accurate predictions. Second, in Study 2 we examined a moderated sequential mediation model, in which the relation between narcissism and perceived learning is sequentially mediated through should counterfactual thinking and hindsight bias, and importantly, this sequential mediation is moderated by prediction accuracy. In Study 3 we ruled out could counterfactual thinking as an alternative explanation for the relationship between narcissism and hindsight bias. Finally, by manipulating should counterfactual thinking in Study 4, our findings suggest that this type of thinking has a causal effect on hindsight bias. We discuss why exhibiting some hindsight bias can be positive after failure. We also discuss implications for eliciting should counterfactual thinking. Our results help explain why narcissists may fail to learn from their experiences.